Climate change, water and agriculture in the Greater Mekong subregion - Johnston, Robyn M.; Lacombe, Guillaume; Hoanh, Chu Thai; Noble, A.D.; Pavelic, Paul; Smakhtin, Vladimir U.; Suhardiman, Diana; Kam, Suan Pheng; Choo, P.S. (International Water Management Institute, 2010)
The impacts of climate change on agriculture and food production in Southeast Asia will be largely mediated through water, but climate is only one driver of change. Water resources in the region will be shaped by a complex mixture of social, economic and environmental factors. This report reviews the current status and trends in water management in the Greater Mekong Subregion; assesses likely impacts of climate change on water resources to 2050; examines water management strategies in the context of climate and other changes; and identifies priority actions for governments and communities to improve resilience of the water sector and safeguard food production.